Workshop Metode dan Materi Pembelajaran Bahasa Inggris, serta Penelitian Tindakan Kelas berdasar Kurikulum Merdeka - Sukarni, Semi; Sudar, Sudar; Setiyono, Junaedi (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
In an effort to facilitate the Kebumen Regency Vocational High School English teachers regarding the implementation of the Merdeka Curriculum, community service is carried out by the English Education Study Program team. The objectives of the community service, i.e.: (1) explaining the concept of project-based learning, learning steps, benefits of PjBL and providing examples of its application in English subjects; (2) describing ways to develop and utilize interesting written text-based materials to design English learning; (3) Providing an explanation of concrete steps for solving learning problems in the classroom through classroom action research (CAR) and other classroom research as an effort to increase teacher professional competence. The service partner is a SMK English teacher in the Kebumen Regency MGMP group which was held at Kebumen State Vocational School 2 on Saturday, March 11 2023. The service activity is held face to face. The results of this activity can be described as follows: (1) participants are able to understand the concept of project-based learning, learning steps, PjBL benefits and examples of application in English subjects; (2 participants were able to develop and utilize interesting written text-based materials to design English learning; (3) participants were able to solve learning problems in class through classroom action research (CAR) and other classroom research.. Keywords: Project-based Learning, classroom action research, workshop